Analisis Determinan dan Motivasi Mahasantri Menggunakan Tabungan di Bank Syariah - Cici Insiyah; Lisniati Lisniati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis study aims to analyze the factors and motivations of the daughters of the intensive IDIA program in using Islamic bank savings. The phenomenon raised in this study concerns the interest in saving for female students who live in a religious environment, namely at Islamic boarding schools and the low interest in saving for female students from the FEBI faculty. To examine this problem, researchers used a qualitative case study approach. The research subjects were IDIA intensive program students who saved at Islamic banks. Data collection is done through observation, interviews and documentation. Based on the results of the study, it is stated that the factors that influence students saving behavior, in Islamic banks, are that generally students save from the remaining pocket money sent by their parents every month. future needs Even though female students have a low level of financial literacy, they still have good self-control in using financial resources, as well as strong religiosity and avoid riba. Meanwhile, the biggest motivation that encourages students to save in Islamic banks is to anticipate future needs. Out of 241 mahasantri, there are 23% of mahasantri who have saving behavior. According to Chen Volpe, a good level of financial literacy is <60%. If the percentage is interpreted into Chen Volpe's level of financial literacy, the level of student financial literacy is very low.Keywords: Factors, Motivation to Save, Mahasantri, Sharia Bank